Medidor de energia elétrica por eventos - Mella, Matheus Janio (2019)
Embedded systems are used in different areas, performing various functionalities, and when combined with the proper software, the whole solution makes it simpler to obtain, understand and visualize data. Electronic measurements of electrical energy enable new possibilities that were not possible with analog systems. Within the context of software-based embedded electronic measurements, this work introduces an electrical energy meter that is able to measure and analyze events generated by the energy consumption of domestic devices. Our methodology and start point is the Protegemed project: an electronic device that detects and analyze events from electric power and differential current of electromedical devices. One of our contributions is a software with graphical interface, in Python, that receives events of voltage and current variation captured by an embedded system consisting of a TM4C129 platform from Texas Instrument. We built a prototype of the embedded system and Python software, and validate it with an electrical reference meter of ELO brand and model ELO2101L. Our results show that it is possible to measure the electric energy from events of current variation, with errors as low as 5% for the calculation of Apparent Energy, and as low as 3% for Active Energy.